Analysis of the heavy metal contents’ effect on steroidal saponins and the anti-breast cancer activity of Paris polyphylla var. yunnanensis - Li, Hai-Ling; Yan, Cui-Ping; Qi, Jun-Sheng; Zhang, Shuo; Guo, Dong-Qin; Gu, Wen-Chao; Wu, Ying-Mei; Wu, Yu; Zhou, Nong (Frontiers in Pharmacology, 2023)
P.polyphylla var. yunnanensis as a near-threatened and ethnic medicine in China, used to be a key ingredient of traditional Chinese medicine, which is treatment of traumatic injuries, sore throat, snakebites, and convulsions for thousands of years. However, there were no reports on the inverse relationship between the contents of heavy metals and saponins and its anti-breast cancer pharmacological activity in P. polyphylla var. yunnanensis. The present study aimed to reveal the characteristics of heavy metal contents, saponins and its anti-breast cancer pharmacological activity and their interrelationships in P. polyphylla var. yunnanensis from different production areas. The heavy metal were highly correlated with the content of steroidal saponins. The overall content of 10 metals in 3 producing origins was C3 > C2 > C1.The total content of 8 steroidal saponins in the extracts of P. polyphylla var. yunnanensis from 3 different origins was C1 > C2> C3. The Pearson correlation study showed that in all of the heavy metals, which the content of Cd and Ba were positively correlated with the main steroidal saponins in P. polyphylla var. yunnanensis. While Al, Cr, Cu, Fe, Zn, As, Hg, Pb showed a negative correlation. In vitro experiment showed that the extracts of P. polyphylla var. yunnanensis from three origins could inhibit the proliferation and induce cell apoptosis of 4T1 cells in a concentration-and time-dependent manner, especially in C1 producing origin. In vivo experiment showed that the extract of P. polyphylla var. yunnanensis from three origins could inhibit the growth of tumors and induce the apoptosis of tumor cells. In this study, we found that with the increase of heavy metal content, the content of steroid saponins and anti-breast cancer activity decreased. The results showed that the high content of total heavy metal may not be conducive to the accumulation of steroidal saponins in P. polyphylla var. yunnanensis, and lead to the low anti-breast cancer activity. The results of this study suggest that the content of heavy metal should be controlled in the artificial cultivation process of P. polyphylla var. yunnanensis.